Targeting Public Services through Unequal Treatment of Unequals - Audun Langørgen (Statistics Norway, Research Department, 2008)
When private goods are publicly provided, government authorities have to determine the distribution of services on recipients. In this paper, the public service provider is assumed to maximize utility defined over service supply to different target groups, given a budget constraint. The production technology is target group specific and depends on the ability of each target group to produce service outcomes. Three benchmark allocation principles are identified: equality of treatment (ET), equality of outcome (EO) and equality of marginal cost (EMC). These principles can be considered to be consistent with special cases of a public preference model, which allows for compromises between different allocation principles. The condition of technological dominance implies that there is a clear-cut equity-productivity trade-off, whereas violations of this condition may reduce the significance of the trade-off.
Keywords: H42; 330; treatment targeting; technological dominance; equity-productivity trade-off; publicly provided private goods; in-kind transfers